Autoestima de mulheres idosas após vivência do luto - Tubin, Sabrina Andreia (2019)
The loss of a spouse entails several emotional and psychosocial changes. We experience a period of reaction to the loss of a beloved one. Grief is considered a process of relocation and readaptation of the subject. It is experienced as hard as the loss of a spouse. Widowhood in the elderly woman, beyond the ordinary factors of mourning, also implies a reorganization of their social role. The aim of the study was to understand the view of elderly widows about what it is to be a woman in a period before and after the loss of a spouse. We sought to analyze the affective relationships and what this loss affected their lives. The approach used in the research was qualitative. The sample included 11 elderly women over 60 years. The technique of collective interview was adopted. Two meetings were held every fifteen days, lasting approximately one hour. Questions were asked regarding life with the spouse, bereavement and overcoming. The average age of widowed elderly women was 71 years old, with an average widow time of 5.7 years. The research results were analyzed through content analysis proposed by de Bardin. The NVivo 12 application was used to structure the analysis categories and subcategories. There was a significant difference in the perception of the elderly about what it is to be a woman in the different periods before and after widowhood. The older women pointed out that they wish their spouses were still alive, but said that if they could go back in time they would have different attitudes towards their roles as wife, mother and wife. Today they have a different worldview than when they were married. They feel more freedom and invest more in themselves and their own self-esteem.